2021
DOI: 10.3389/fimmu.2021.623256
|View full text |Cite
|
Sign up to set email alerts
|

A20 Establishes Negative Feedback With TRAF6/NF-κB and Attenuates Early Brain Injury After Experimental Subarachnoid Hemorrhage

Abstract: Nuclear factor (NF)-κB–ty -50mediated neuroinflammation plays a crucial role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). As an important negative feedback regulator of NF-κB, A20 is essential for inflammatory homeostasis. Herein, we tested the hypothesis that A20 attenuates EBI by establishing NF-κB–associated negative feedback after experimental SAH. In vivo and in vitro models of SAH were established. TPCA-1 and lentivirus were used for NF-κB inhibition and A20 silencing/overexpression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…An experimental SAH model was established by injecting autologous arterial blood into the prechiasmatic cistern of the optic chiasm as described previously, with minor modifications ( Deng et al, 2021 ). The mice were anesthetized using 100% O 2 containing 2% isoflurane and fixed on a stereotaxic apparatus while maintaining anesthesia with 1% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…An experimental SAH model was established by injecting autologous arterial blood into the prechiasmatic cistern of the optic chiasm as described previously, with minor modifications ( Deng et al, 2021 ). The mice were anesthetized using 100% O 2 containing 2% isoflurane and fixed on a stereotaxic apparatus while maintaining anesthesia with 1% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, L-NAME, which was used to induce HCMB, was only used in the HCMB group from days 1 to 28 and was added to drinking water at a dose of 100 mg/kg/day ( 24 , 25 , 27 29 ). During the experiment, if we found that some mice showed signs of reduced neurological function, we performed MRI on the mice with neurological function scores below 16 (according to the modified Garcia score) ( 30 , 31 ) and excluded them if they were considered to have ICH. Prior to the formal blood pressure measurement, we anesthetized the mice using barbiturates, immobilized them on the MRI instrument after they were better anesthetized, and then performed MRI measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Nissl staining was used to evaluate neuronal damage in the ipsilateral cortex, as described previously ( Deng et al, 2021 ). Briefly, at 24 h after SAH, the mice were deeply anesthetized and transcardially perfused with 50 ml of phosphate-buffered saline (PBS; 0.1 M) followed by 50 ml of 4% paraformaldehyde (PFA; pH 7.4).…”
Section: Methodsmentioning
confidence: 99%